2017
DOI: 10.1504/ijlic.2017.086390
|View full text |Cite
|
Sign up to set email alerts
|

Modified value-added intellectual coefficient (MVAIC) and traditional financial performance of Indonesian biggest companies

Abstract: The purpose of this study is to examine the influences of intellectual capital performance-measured with modified value added intellectual coefficient (MVAIC)-to four traditional financial performances: return on assets, return on equity, market to book value and price earnings ratio. The data were drawn from 50 biggest market capitalisation companies listed in the Indonesia stock exchange for 8 years (2007-2014). It is an empirical study using WarpPLS 3.0 for the data analysis. The finding shows that: MVAIC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 22 publications
6
36
1
6
Order By: Relevance
“…The higher the intellectual capital performance has in line with the better the financial performance (Ulum, Kharismawati and Syam, 2017). IC is not only had a positive influence on the company's financial performance for the current year, but it can also predict the company's future financial performance.…”
Section: Effect Of Intellectual Capital Performance On Company Financmentioning
confidence: 92%
See 2 more Smart Citations
“…The higher the intellectual capital performance has in line with the better the financial performance (Ulum, Kharismawati and Syam, 2017). IC is not only had a positive influence on the company's financial performance for the current year, but it can also predict the company's future financial performance.…”
Section: Effect Of Intellectual Capital Performance On Company Financmentioning
confidence: 92%
“…The relationship between IC and company performance has been proven empirically by several previous researchers. Ulum, Kharismawati, and Syam (2017) examine the effect of MVAIC on the company's traditional financial performance and found that MVAIC has a positive effect on the company's financial performance. Research of Hermawan, Hanun, and Pamungkas (2019) on financial sector companies with high IC intensity found that VAIC has a positive effect on financial performance and market performance.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Znalazła szerokie zastosowanie w badaniach empirycznych, zyskując zarówno zwolenników, jak i przeciwników. VAIC TM traktowany jest jako miara wydajności kapitału intelektualnego (ICP -Intellectual Capital Performance) [Ulum, Kharismawati, Syam 2017] i określany przez Mavridisa [2004], Kamatha [2007] i Uluma [2009b] jako wskaźnik wydajności biznesowej.…”
Section: Wstępunclassified
“…Przeprowadzenie badania w tym przypadku niesie ze sobą istotne implikacje dla praktyki biznesowej. Zastosowanie metodyki opracowanej przez Pulicia oraz poddanej pewnym modyfikacjom [Ulum i in. 2017;Maji, Goswami 2017] podyktowane było przede wszystkim celem badania oraz tym, że metoda ta znajduje zastosowanie w przypadku jednostek, których akcje nie stanowią przedmiotu obrotu giełdowego.…”
Section: Efektywność Kapitału Intelektualnego Oraz Wpływ Mvaic Na Wynunclassified